(untitled) (Human Geographies – Journal of Studies and Research in Human Geography, 2025)
Since the beginning of the COVID-19 pandemic, the news reports on it have been accompanied by maps. Similarly to weather maps, they became part of our daily news feed. The newspapers’ maps reporting on the COVID-19 pandemic often use the same or similar data to depict the current state of the spread within a national territory. However, the designs of the maps vary between different news outlets. These differences were analysed using the documentary method introduced by sociologist Ralf Bohnsack, using the case study of six COVID-19 maps published in Mexican national newspapers. The analysis resulted in a typology of maps, which proposed different readings of the infographic itself when it comes to the aspects of (1) the cognitive process it supposedly triggers, (2) the kind of information it contains, (3) the usefulness for the viewer/reader, and (4) whether the author or the reader has the authority over the reading/learning process.